MALE AND FEMALE TEACHER’S INITIATION IN ENGLISH CLASSROOM INTERACTION - Anatasya Gisela Sibarani; Siti Aisah Ginting; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2018)
This study was about male and female teacher’s initiation in English classroom interaction. The aims of this study were (1) to find out the types of male and female teacher’s initiations used in English classroom interaction based on Sinclair and Coulthard Model, (2) to find out the reason why male and female teacher used the types of initiation. The design of the research used qualitative research. To answer the problems of the study, the data were collected in three ways by observing, video recording and interviewing. The data were analyzed based on Sinclair and Coulthard theory (1975). The result of this study were the following, (1) there were nine types of initiation used by male and female teacher in English classroom interaction, namely, boundary, teacher inform, teacher direct, teacher elicit, check, re-initiation (i), re-initiation (ii), listing and repeat. (2) the reasons in use of types initiation by male and female teacher. Those were affected by male and female teacher belief which belongs to the presage category and context category which refers to the class in which the teaching process takes place. They had different ways when doing initiation in English classroom interaction, which is they had their own ways in doing interaction with the students. Even though they had different ways but their aim just making the students comprehended and could knew what the teachers said.Keywords: Initiation, Gender, Classroom Interaction